The Impact of Website Usability and Mobile Optimization on Customer Satisfaction and Sales Conversion Rates in E-commerce Businesses in Indonesia - Nawir, Fadliyani; Hendrawan, Satya Arisena (The Eastasouth Journal of Information System and Computer Science, 2024)
This study investigates the impact of website usability and mobile optimization on customer satisfaction and sales conversion rates in e-commerce businesses in Indonesia. Utilizing a quantitative approach, data were collected from 170 respondents using a Likert scale ranging from 1 to 5. The analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results indicate that all hypothesized relationships are positive and significant. Specifically, improvements in website usability and mobile optimization significantly enhance customer satisfaction, which in turn positively influences the sales conversion rate. The findings underscore the critical importance of optimizing website usability and mobile interfaces to boost customer satisfaction and drive higher sales conversions in the competitive e-commerce landscape of Indonesia.